The Holly : five bullets, one gun, and the struggle to save an American neighborhood - Rubinstein, Julian (Farrar, Straus and Giroux, 2021)
"A history of the Denver neighborhood known as the Holly and the controversial anti-gang activist Terrance Roberts"--